2012
DOI: 10.1111/j.1556-4029.2012.02243.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Dependence and Criminal Behavior: Preliminary Results of an Association Study of Environmental and Genetic Factors in an Italian Male Population

Abstract: The aim of this study is to propose an innovative approach evaluating the connection between alcohol use disorders and criminal behavior. The research, structured as a case-control study, was based on the analysis of environmental (social variables) and genetic factors (single nucleotide polymorphisms of glutamic acid decarboxylase) in a population (N = 173) of Italian alcohol-dependent men. Group 1 (N = 47, convicted subjects) was compared with Group 2 (N = 126, no previous criminal conduct). Grade repetition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Inclusion and exclusion criteria, sample selection, methodological approach, and classification of felonies have already been described by the authors in a previous study (3). Environmental factors related to criminal behavior were selected according to the criteria described in the same article previously mentioned (3).…”
Section: Subjects and Phenotype Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Inclusion and exclusion criteria, sample selection, methodological approach, and classification of felonies have already been described by the authors in a previous study (3). Environmental factors related to criminal behavior were selected according to the criteria described in the same article previously mentioned (3).…”
Section: Subjects and Phenotype Assessmentmentioning
confidence: 99%
“…Group 2, n = 139, no history of criminal conduct, recruitment from AD treatment centers in Dolo, Rovigo, and Cittadella (Veneto) and the Section of Forensic Toxicology, University of Padova. Inclusion and exclusion criteria, sample selection, methodological approach, and classification of felonies have already been described by the authors in a previous study (3). Environmental factors related to criminal behavior were selected according to the criteria described in the same article previously mentioned (3).…”
Section: Subjects and Phenotype Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A US study found that grade repetition was independently associated with increased risk of behavior problems among white children and adolescents [ 10 ]. Despite a growing evidence base that links grade repetition to adverse behavioral outcomes [ 11 13 ], the literature includes mostly small observational studies of specific behavioral outcomes, such as bullying victimization, and provides inconsistent results [ 14 , 15 ]. One study found no differences in bullying victimization between socially promoted and retained students in public schools [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A US study found that grade repetition was independently associated with increased risk of behavior problems among white children and adolescents [10]. Despite a growing evidence base that links grade repetition to adverse behavioral outcomes [11][12][13], the literature includes mostly small observational studies of specific behavioral outcomes, such as bullying victimization, and provides inconsistent results [14,15]. One study found no differences in bullying victimization between socially promoted and retained students in public schools [14].…”
Section: Introductionmentioning
confidence: 99%